2008
DOI: 10.1161/strokeaha.108.521583
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fever on Outcome in Patients With Stroke and Neurologic Injury

Abstract: Background and Purpose-Many studies associate fever with poor outcome in patients with neurological injury, but this relationship is blurred by divergence in populations and outcome measures. We sought to incorporate all recent scholarship addressing fever in brain-injured patients into a comprehensive meta-analysis to evaluate disparate clinical findings. Methods-We conducted a Medline search for articles since January 1, 1995 (in English with abstracts, in humans) and hand searches of references in bibliogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
221
2
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(246 citation statements)
references
References 23 publications
15
221
2
8
Order By: Relevance
“…Moreover, a correlation has been found between increases in temperature and higher values of intracranial pressure in patients after SAH and head trauma [13]. A collective meta-analysis involving 14,431 patients with brain injuries has revealed that fever correlates with poorer prognosis and higher mortality [34].…”
Section: Consequences Of Central Fevermentioning
confidence: 99%
“…Moreover, a correlation has been found between increases in temperature and higher values of intracranial pressure in patients after SAH and head trauma [13]. A collective meta-analysis involving 14,431 patients with brain injuries has revealed that fever correlates with poorer prognosis and higher mortality [34].…”
Section: Consequences Of Central Fevermentioning
confidence: 99%
“…of brain injury, 9,25 early recognition of this condition and modulation of the physiopathological mechanisms leading to dysthermia may be part of strategies aimed at limiting systemic complications, primary and secondary neuronal injury, and improving long-term outcomes. 16 Although much is known about the effects of dysthermia on neurological outcomes after brain injury, only limited data based on neurological diagnosis are available for addressing the epidemiology and risk factors of this phenomenon.…”
mentioning
confidence: 99%
“…Previous studies have shown that body temperature elevation is associated with the clinical severity and prognosis of stroke (12)(13)(14). Elevated body temperature is also a risk factor for the hemorrhagic transformation of acute ischemic stroke when recombinant tissue-type plasminogen activator treatment is not applied to patients (15).…”
Section: A B Cmentioning
confidence: 99%